The Analysis Study of Detection of Gonorrhea among HIV Infected Patients: A Comprehensive Systematic Review - Hutabarat, Ruth Bethania Dayu; Megantara, Fauzie Ilhamsyah (International Medical Journal Corp. Ltd, 2024)
Background: Sexually transmitted diseases (STDs) are one the major public health concern in the world. Neisseria gonorrhea is an obligate human pathogen responsible for gonorrhea as one of the commonest sexually STDs. The aim: The aim of this study to show about detection of gonorrhea among HIV infected patients. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Early detection of sexually transmitted diseases is very useful for starting treatment early which will affect the outcome and prognosis of a disease such as gonorrhea, especially in patients suffering from HIV.